PENGARUH PERSEPSI HARGA DAN CITA RASA TERHADAP KEPUASAN KONSUMEN TOKO BREAD.CO CABANG CIBADAK - Sri Rahayu; Abu Bakar Ashidiqy (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2023)
Competition in the business world, especially the food industry, must be able to achieve goals by creating and retaining consumers who are oriented towards customer satisfaction. The purpose of this study was to determine the effect of price and taste perceptions on customer satisfaction at Bread.co stores, Cibadak Branch. This study used a quantitative approach and a total sample of 60 people. The analytical method used in this study is multiple linear regression to analyze the effect of price and taste perceptions on consumer satisfaction. The results of the study show that partially perceived price and taste have a significant effect on consumer satisfaction